55.1: Invited Paper: Photolithographic patterning of OLED and OPD for invisible sensor integration in mobile display. (24th February 2021) - Ke, Tung-Huei; Georgitzikis, Epimitheas; Alvarez, Gema Molina; Vandenplas, Erwin; Hagelsieb, Luis Moreno; Akkerman, Hylke; Shanmugam, Santhosh; van Breemen, Albert; Heremans, Paul; Malinowski, Pawel E.
Abstract : We apply a photolithographic patterning process to integrate a green phosphorescent organic light emitting diode (OLED) with a polymer‐based organic photodetector (OPD) side‐by‐side with resolution up to 635 ppi. The characteristics of OLED and OPD before and after patterning are investigated. The crosstalk between OLED and OPD subpixels and the linearity of the integrated OPD under different luminance are also studied. The results indicate that photolithography enabled integration is an encouraging route of organic and hybrid electronics (OHEs) manufacturing.